Introduction to Cultural Entrepreneurship: Cultural Entrepreneurship in Developing Countries - Toghraee, Mohamad Taghi; Monjezi, Mahsa (International Review of Management and Marketing, 2017)
Up to now, no evaluation has been made about crucially main impacts of entrepreneurship and entrepreneurial approaches to the support of creative and cultural economy in developing countries. Great potentials of cultural industries are not still utilized, and no attention is made to them regarding economic profitability. The most crucial determinants of inappropriately competitive conditions concerning innovation in developing countries, which require global help, are education issues, poverty, and lack of related institutions. Moreover, a continuum of cultural productions is delicate. There are weak steps and stages for promotion, branding, distribution, and ownership support of cultural productions due to not only lack of integration but also a lack of artists’ knowledge about these processes. This study examines the role of cultural entrepreneurship in the sustainability of artists and creative organizations. The following questions are addressed accordingly: To what extent can cultural entrepreneurship capacities act as a determinant for the development of artists and artistic areas of activities; Is this phenomenon definable and learnable; How can cultural and artistic values be understood by entrepreneurial capacities in a cultural context. Entrepreneurship of cultural and creative industries combines two independent trends: Art as a content-based and immaterial value and entrepreneurship as a supporter of immaterial values. By this basis in mind and the social responsibility of entrepreneurs, cultural entrepreneurship can run a cultural and creative organization, carry out a strategically cultural mission, face risks to the creation of balance between managerial values and innovation and make a contribution to critical infrastructure. Keywords: Creative economy, cultural values, creative industries, cultural industries, cultural entrepreneurship. JEL Classifications: M21, Z110